Fatty Acid Composition of Hepatopancreas and Gonads in Both Sexes of Orange Mud Crab, Scylla olivacea Cultured at Various Water Flow Velocities - Muhammad Taufik; Ismail Shahrul; Abdul Rahman Mohd Nordin; Mhd Ikhwanuddin; Ambok Bolong Abol-Munafii (Tropical Life Sciences Research, 2020)
Nutritional quality of the hepatopancreas and gonads of orange portunid mud crab, Scylla olivacea was evaluated for each gender under four treatment of different water velocities (0, 20, 40 and 60 cm s–1), in terms of nutrient reserve and nutrient for reproduction. About 56 crabs were used in this study in which fatty acids composition was analysed using gas chromatography mass-spectrometry (GC-MS). For hepatopancreas analysis, monounsaturated fatty acids (MUFAs) were present in the highest fatty acids concentration, followed by polyunsaturated fatty acids (PUFAs) and, saturated fatty acids (SFAs). However, long-chain polyunsaturated fatty acids (LC-PUFAs) were displayed in low concentration in the hepatopancreas. Total fatty acid (TFAs) composition was significantly higher at moderate velocity of 20 cm s–1 compared to other water velocity treatments. For gonad analysis, 20 cm s–1 showed the highest TFA concentration of 93.34 mg g–1 while, the lowest concentration of 3.90 mg g–1 occurred at 0 cm s–1. There were significant differences in male and female crab’s fatty acids contents of gonads at all flow velocities challenged (p < 0.05). PUFAs and MUFAs were dominant while, SFAs were observed at low concentration. This study revealed that, concentration of PUFAs increased as gonad maturation increased. The decreasing concentration of hepatopancreas fatty acids over the culture period indicated that nutrient was shifted from the hepatopancreas, to be used as energy reserved to gonads for further growth of eggs and offspring. The linkages between water flow strength, hepatopancreas, and gonad fatty acids concentrations, is fundamental knowledge useful in establishing efficient habitat velocities selection which will improve aquaculture production of mud crabs with high quality broodstock. Kualiti pemakanan hepatopancreas dan gonad ketam lumpur portunid jingga, Scylla olivacea dinilai untuk setiap jantina di bawah empat perlakuan dengan halaju air yang berbeza (0, 20, 40 dan 60 cm s–1), dari segi simpanan nutrien dan nutrien untuk pembiakan. Kira-kira 56 ketam digunakan dalam kajian ini di mana komposisi asid lemak dianalisis menggunakan kromatografi gas-spektometri jisim (GC-MS). Untuk analisis hepatopancreas, asid lemak tak tepu mono (MUFAs) terdapat dalam kepekatan asid lemak tertinggi, diikuti oleh asid lemak tak tepu ganda (PUFA) dan asid lemak tepu (SFA). Walau bagaimanapun, asid lemak tak tepu ganda rantai panjang (LC-PUFAs) ditunjukkan dalam kepekatan rendah pada hepatopankreas. Jumlah komposisi asid lemak (TFA) jauh lebih tinggi pada halaju sederhana 20 cm s–1 berbanding dengan rawatan halaju air yang lain. Untuk analisis gonad, 20 cm s–1 menunjukkan kepekatan TFA tertinggi 93.34 mg g–1 sementara, kepekatan terendah 3.90 mg g–1 berlaku pada 0 cm s–1. Terdapat perbezaan yang signifikan dalam kandungan asid lemak ketam jantan dan betina pada gonad pada semua cabaran halaju air (p < 0.05). PUFA dan MUFA dominan sementara, SFA diperhatikan pada kepekatan rendah. Kajian ini menunjukkan bahawa, kepekatan PUFA meningkat seiring bertambahnya kematangan gonad. Penurunan kepekatan asid lemak hepatopancreas selama tempoh kultur menunjukkan bahawa nutrien dialihkan dari hepatopancreas, untuk digunakan sebagai tenaga yang disediakan untuk gonad untuk pertumbuhan telur dan keturunan lebih lanjut. Hubungan antara kekuatan aliran air, hepatopankreas dan kepekatan asid lemak gonad, adalah pengetahuan asas yang berguna dalam mewujudkan pemilihan kecepatan habitat yang cekap yang akan meningkatkan pengeluaran akuakultur ketam lumpur dengan bahan makanan berkualiti tinggi.